1972
DOI: 10.1126/science.177.4055.1203
|View full text |Cite
|
Sign up to set email alerts
|

A New, Long-Lasting Competitive Inhibitor of Angiotensin

Abstract: An analog of angiotensin II, [Sar(1), Ile(8)]-angiotensin II, has a potent and long-lasting competitive antagonistic effect against angiotensin II when tested for its myotropic action on the isolated rabbit aorta and for its effect on blood pressure in anesthetized cats and dogs. Compared to [Ile(8)]-angiotensin II, the new analog has equal antagonistic potency on the isolated system but a much greater potency in vivo. It is assumed that sarcosine in position 1 protects the peptide against enzymatic degradatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
2

Year Published

1974
1974
2009
2009

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(29 citation statements)
references
References 8 publications
1
26
0
2
Order By: Relevance
“…14) , losartan, a selective non-peptide AT 1 receptor antagonist 13) , and PD-123,319 ditrifluoroacetate, a potent selective non-peptide AT 2 receptor antagonist 13) , were respectively applied to cells at concentrations of 10M through perfusate. Losartan was a gift from Merk & Co., Inc.…”
Section: Methodsmentioning
confidence: 99%
“…14) , losartan, a selective non-peptide AT 1 receptor antagonist 13) , and PD-123,319 ditrifluoroacetate, a potent selective non-peptide AT 2 receptor antagonist 13) , were respectively applied to cells at concentrations of 10M through perfusate. Losartan was a gift from Merk & Co., Inc.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, endothelium-derived factors are not responsible for the generation of Ca¥ ripples. We then investigated the effect of 10 nÒ [Sar 1 ,IleÌ]-Ang II, an Ang II antagonist (Turker et al 1972). Indeed, Ca¥ ripples were reversibly abolished by the antagonist (Fig.…”
Section: Characterization Of Ca¥ Ripplesmentioning
confidence: 99%
“…For example, it has been reported that some peptide analogues did not behave in a simple competitive manner with All, but produced 'non-competitive' or 'insurmountable' antagonism (Regoli et al, 1974;Freer et al, 1980a,b;Koziarz & Moore, 1989; Bovy & Blaine, 1989). The antagonism of [Sar',Ile8]AII, however, has been described as both 'essentially competitive' (Turker et al, 1972) and 'pseudo-irreversible' (Scanlon & Moore, 1988). Most peptide analogues have been found to produce partial agonist effects in vivo (Streeten & Anderson, 1984;Holck et al, 1989; and some in vitro (Regoli et al, 1974;Scanlon et al, 1984;Criscione et al, 1990).…”
Section: Introductionmentioning
confidence: 99%